A Political-Theological Issue: Is Kemalism a Civil Religion or a Political Religion? - Gülbeyaz Karakuş (Journal of Economy Culture and Society, 2023)
This article examines early Kemalism from a political-theological perspective. In the context of the religion-politics relationship of the modern nation-state model, the approach of Kemalism toward religion and the concept of “national religion” are discussed. In addition, “secular sacredness” produced through citizenship, the instrumentalization of religion, and legitimacy are also discussed. These secular sacraments, which emerge as a political-theological issue, are defined as a civil or political religion. This article discusses the transitivity between these two approaches and Kemalism. The main question of the article is whether Kemalism has a subjective approach to the oscillation between civil religion and political religion. It also attempts to reveal whether the emerging “national religion” is a reflection of the established religion or offers a different understanding. The answer is sought as to whether the national religion, which was intended to be fostered by liquidating the established religion, has an instrumental function. In the ideology of Kemalism, there has been a process in which religion has not been completely eliminated but defined through the concept of a secular or national religion. In this context, it is questioned whether there is no clear distinction between a political religion and a civil religion, peculiar to the totalitarian regimes, and whether there a new “theology” has been established which is contrary to the established religion.